O.P.P.: How Occupy's Race-Based Privilege May Improve Fourth Amendment Jurisprudence for All - Herbert, Lenese C. (2011)
This Article submits that Occupy’s race problem could, ironically, prove to be a solution if protesters grow more serious about exposing the injury of political subordination and systems of privilege that adhere to the criminal justice system. Privilege is a “systemic conferral of benefit and advantage [as a result of] affiliation, conscious or not and chosen or not, to the dominant side of a power system.” Accordingly, now that police mistreatment affects them personally, Occupy may finally help kill a fictitious Fourth Amendment jurisprudence that ignores oppression through improper policing based on racial stigma. Occupy may also help usher in an era in which courts are free(er) to produce a more legitimate jurisprudence regarding police conduct that inspires greater confidence in reality-based adjudications of modern (albeit longstanding) police misconduct, irrespective of race, as the current “[s]ystems of privilege maintain hierarchies of inequality, adversely impacting the possibility of full societal participation.